Understanding ministerial accountability in the New Pentecostal Prophetic churches - Sello E. Letswalo; Marilyn Naidoo (HTS Teologiese Studies/Theological Studies)
Within churches, congregational health and well-being require not only efficient church leadership, but also prudent church management. Good leadership structures influence governance and ministry tasks, and the awareness of accountability is a vital concept within organisations. It shapes the entire managerial progression influencing values, objectives and practices. This article reports on a study to establish the understanding of ministerial accountability in the New Prophetic Pentecostal churches. Findings reveal a unique understanding of leaders’ personal accountability, communal and cultural ministry practices and public accountability towards the broader community. This article speaks to the normative task of the Church and creates a new reflection on ministerial accountability and ethical practices as well as implications for congregational development broadly.